Komposisi Tubuh Member Senam Aerobik di Sanggar Se-Kecamatan Gunungpati - Sunyari Sunyari; Ipang Setiawan (Universitas Negeri Semarang, 2023)
The purpose of the research is that gymnastic members perform aerobic exercise activities to form a good body composition, namely Body Mass Index (BMI) and a good percentage of body fat. The purpose of this study was to determine and identify the body composition of members of aerobic exercise in a studio in the district of Gunungpati. Descriptive quantitative research method with survey techniques and research design used is a cross-sectional research design, the subjects in this study are members of the gymnastics studio in the district of Gunungpati. Collecting data using total sampling technique using survey data collection methods on body composition. Then the data analysis technique using descriptive statistics with percentages. The conclusion from this study is that the average Body Mass Index (BMI) of gymnastics members is 26.57 kg/m² and is included in the obesity category I. The average body fat percentage of gymnastic members is 26.5% and is included in the normal category (fat average). And there is a relationship between Body Mass Index (BMI) and body fat percentage of r = 0.742. Suggestions given by researchers are:1) For members, it is hoped that they can be more diligent in participating in aerobic exercise classes, because if these gymnastic activities can run continuously, it will have a positive impact on members.2) For instructors, it is hoped that they will be more active in justifying members' movements, providing direction and motivation to members